EEG Patterns in Angelman Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The sensitivity of the electroencephalogram (EEG) in the diagnosis of Angelman syndrome (AS) was studied in 26 patients (3/1 : F/M ratio) at the University of Sao Paulo Medical School, Brazil.